Pemanfaatan E-Commerce Dalam Pengembangan Usaha Bawang Goreng Di Desa Oloboju Kabupaten Sigi - Nurfadilla Nurfadilla; Syamsul Bachri; Elimawaty Rombe; Farid Farid (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
The use of information technology, especially e-commerce, has brought about fundamental changes in the way business is conducted. This article presents a literature review of how business development can be achieved through implementing e-commerce strategies. E-commerce not only provides greater access to consumers but also opens up new opportunities for business actors to increase operational efficiency, optimize supply chains, and expand market share. The discussion began by detailing recent developments in e-commerce technology and their impact on business transformation. Next, the focus is placed on business development strategies that can be implemented by business people to optimize the benefits of e-commerce. This research highlights the importance of adaptation and innovation as key elements in facing changing market dynamics. By understanding the potential of e-commerce and implementing the right strategies, businesses can gain a significant competitive advantage and achieve long-term success.